PpWRKY33 positively regulates PpPGIP1 to enhance defense against Monilinia fructicola in peach fruit - Gao, Yinli; Wei, Yingying; Chen, Yi; Jiang, Shu; Ye, Jianfen; Xu, Feng; Jin, Peng; Ding, Phebe; Shao, Xingfeng (Elsevier B.V., 2024)
In plant-pathogen interactions, numerous pathogens secrete polygalacturonase (PG) to degrade plants cell walls, whereas plants produce PG-inhibiting protein (PGIP) that specifically binds to pathogen-derived PG to inhibit its activity and resist pathogen infection. In the present study, we dshowed that PpPGIP1 was significantly upregulated in peaches after Monilinia fructicola infection, and the prokaryotic expression of the PpPGIP1 protein inhibited M. fructicola by mitigating its PG activity. Transient overexpression of PpPGIP1 in peaches significantly enhanced their resistance to M. fructicola. PpPGIP1 promoter had several W-box the defense elements that can bind to WRKY transcription factors. Transcriptome analysis identified 20 differentially expressed WRKY genes, including the classic disease resistance gene WRKY33. PpWRKY33 is significantly upregulated in M. fructicola infected peaches. PpWRKY33 is localized in the nucleus and can bind to the W-box in the PpPGIP1 promoter to transcriptional activate the expression of PpPGIP1. Transient overexpression PpWRKY33 upregulated PpPGIP1 expression in peaches, and silencing PpWRKY33 decreased the PpPGIP1 expression. These results indicated that PpPGIP1 positively regulates fungal disease resistance in peaches and is transcriptionally activated by PpWRKY33. These findings reveal the disease resistant role of PpPGIP1 in peaches, and provide new insights into its transcriptional regulation.